Anthocyanin supplementation in adults at risk for dementia: a randomized controlled trial on its cardiometabolic and anti-inflammatory biomarker effects - Miguel German Borda; Robinson Ramírez-Vélez; Felipe Botero-Rodriguez; Jonathan Patricio-Baldera; Chiara de Lucia; Ilaria Pola; George E. Barreto; Khadija Khalifa; Anne Katrine Bergland; Miia Kivipelto; Tommy Cederholm; Henrik Zetterberg; et al. (GeroScience, 2025)
Anthocyanins are dietary flavonoids shown to have a therapeutic capacity to mitigate inflammation and oxidative stress. The present secondary analyses from the “Anthocyanins in People at Risk for Dementia Study” were aimed at (I) determining the intervention’s effect on blood-based markers of cardiovascular disease and inflammation and (II) evaluating whether baseline factors such as age, sex, inflammation, or cardiometabolic score may moderate the intervention’s effect on inflammatory status. This study was an ancillary, 24-week randomized, double-blind, placebo-controlled Phase II trial. Sub-sample participants ( n = 99), aged 60–80 years with mild cognitive impairment or cardiometabolic disorders, were randomized to receive either 320 mg/day of anthocyanins or placebo. The biomarkers analyzed included inflammatory biomarker assessment (IL − 6, IL − 8, IL − 10, IL − 1b, TNF − α, IFN − γ), and C-reactive protein (CRP), as well as albumin, thrombocytes, cholesterol, LDL, HDL, and triglycerides, which were longitudinally compared between both groups. Baseline characteristics were balanced between the groups. ANCOVA analyses reveal 24-week differences favoring the anthocyanin treatment in LDL cholesterol levels (ƞp 2 = 0.078; p = 0.015), cardiometabolic score (ƞp 2 = 0.073; p = 0.021), CRP levels (ƞp 2 = 0.417; p = 0.0001), IL − 6 (ƞp2 = 0.085; p = 0.015), IL − 1b (ƞp 2 = 0.058; p = 0.037), and Inflam z-score 5 (ƞp 2 = 0.059, p = 0.004). Moderation analysis demonstrated that the inflammatory score at baseline was a significant predictor of the effect of the intervention on the CRP levels. Anthocyanin supplementation reduces CRP and cardiovascular disease biomarkers in individuals at risk of dementia, especially when there is increased inflammation at baseline. ClinicalTrials.gov study identifier: NCT03419039.

The impacts of social determinants of health and cardiometabolic factors on cognitive and functional aging in Colombian underserved populations - Hernando Santamaria-Garcia; Sebastian Moguilner; Odir Antonio Rodriguez-Villagra; Felipe Botero-Rodriguez; Stefanie Danielle Pina-Escudero; Gary O’Donovan; Cecilia Albala; Diana Matallana; Michael Schulte; Andrea Slachevsky; Jennifer S. Yokoyama; Katherine Possin; et al. (GeroScience, 2023)
Global initiatives call for further understanding of the impact of inequity on aging across underserved populations. Previous research in low- and middle-income countries (LMICs) presents limitations in assessing combined sources of inequity and outcomes (i.e., cognition and functionality). In this study, we assessed how social determinants of health (SDH), cardiometabolic factors (CMFs), and other medical/social factors predict cognition and functionality in an aging Colombian population. We ran a cross-sectional study that combined theory- (structural equation models) and data-driven (machine learning) approaches in a population-based study ( N = 23,694; M = 69.8 years) to assess the best predictors of cognition and functionality. We found that a combination of SDH and CMF accurately predicted cognition and functionality, although SDH was the stronger predictor. Cognition was predicted with the highest accuracy by SDH, followed by demographics, CMF, and other factors. A combination of SDH, age, CMF, and additional physical/psychological factors were the best predictors of functional status. Results highlight the role of inequity in predicting brain health and advancing solutions to reduce the cognitive and functional decline in LMICs.